Bariery rozwoju niedrzewnej produkcji leśnej w wybranych krajach europejskich - Kalinowski, Michał (Leśne Prace Badawcze, 2010)
The barriers to development of non-wood forest products and services identified in many countries’ reports from the COST Action E30 were grouped and classified into main categories, as follows: political (timber-dominated education, free access to resources), connected with attitudes and behaviour of forest owners/entrepreneurs (mental barriers of forest owners to new forest uses, farmers’ focus on agricultural production, disinterest of 'new’ or urban owners in this income, limited entrepreneurial orientation of forest owners), technical (low and irregular concentration of resources, high variability of yield in time and space), economical (squeezing forest products and services out of the market by non-forest alternatives, under-developed domestic markets, creation of added value is limited, problems with quality control and creating of integrated products) and social (lack of seasonal workers and low population density in rural areas).